Comprehensive genome sequence analysis of Ralstonia solanacearum gd-2, a phylotype I sequevar 15 strain collected from a tobacco bacterial phytopathogen - Xiao, Zhiliang; Li, Guangcan; Yang, Aiguo; Liu, Zhengwen; Ren, Min; Cheng, Lirui; Liu, Dan; Jiang, Caihong; Wen, Liuying; Wu, Shengxin; Cheng, Yazhi; Yu, Wen; et al. (Frontiers in Microbiology, 2024)
Plant bacterial wilt is an important worldwide disease caused by Ralstonia solanacearum which is a complex of species. In this study, we identified and sequenced the genome of R. solanacearum strain gd-2 isolated from tobacco. Strain gd-2 was identified as R. solanacearum species complex (RSSC) phylotype I sequevar 15 and exhibited strong pathogenicity to tobacco. The genome size of gd-2 was 5.93 Mb, including the chromosomes (3.83 Mb) and the megaplasmid (2.10 Mb). Gene prediction results showed that 3,434 and 1,640 genes were identified in the chromosomes and plasmids, respectively. Comparative genomic analysis showed that gd-2 exhibited high conservation with ten highly similar strain genomes and the differences between gd-2 and other genomes were mainly located at positions GI12-GI14. 72 type III effectors (T3Es) were identified and RipAZ2 was a T3E specific to gd-2 compared with other eight sequenced strain. Our study provides a new basis and evidence for studying the pathogenic mechanism of R. solanacearum.